KEPRIBADIAN TOKOH UTAMA LEGOSHI PADA ANIME BEASTARS - Darmawan, I Wayan Andi; Meidariani, Ni Wayan; Meilantari, Ni Luh Gede (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2022)
This research aims to knowing the personality of the main character Legoshi in the Beastars anime. The theory used is the theory of literary psychology, namely Sigmund Freud's psychoanalytic personality theory. The source of data used in this study is the primary data source in the form of anime using the listen and note method. The data obtained were then analyzed using a qualitative descriptive method. Based on the results of the analysis of the data obtained, there are three personality structures in Legoshi, namely the id, ego, and superego.